2013
DOI: 10.1134/s0012500813030087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preliminary compression and uniform shear on the deformation behavior of a filled polymer nanocomposite in orientation stretching

Abstract: In this work, for the first time, we described the possibility of eliminating the brittle fracture of filled polymer nanocomposites in orientation stretching by preliminary compression deformation and small uni form shear deformation before stretching. After such a treatment, the polymer composite material becomes capable of experiencing larger deformation elonga tions in stretching.Orientation stretching is known to be an efficient way to improve the mechanical properties of polymer materials [1]. However, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…It was previously established [2] that, if a similar "brittle" initial composite is subjected to uniform shear deformation, then its strength characteristics significantly increase, which was also observed in this work for the studied PENG specimens.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…It was previously established [2] that, if a similar "brittle" initial composite is subjected to uniform shear deformation, then its strength characteristics significantly increase, which was also observed in this work for the studied PENG specimens.…”
supporting
confidence: 83%
“…However, such stretching of polymer composites filled with various dispersed fillers is often accompanied by their brittle fracture even early in the deformation [2].In this work, for the first time, we described the possibility of producing strengthened oriented highly filled electrically conductive polymer nanocomposites under uniform shear conditions so that the rupture strength of these composites is an order of magnitude higher than that of non oriented composites of the same composition.We studied electrically conductive specimens of polymer composites of various compositions that were produced by filling a nascent reactor powder of ultra high molecular weight polyethylene (UHMWPE) of a nodular morphological structure (with a molecular weight of 5 × 10 6 and a bulk density of the reactor pow der of 0.058 g/cm 3 ) [1] with a commercial electrically conductive graphene nanopowder (GN) of grade AO 4 containing 60 nm thick flakes (Graphene Laborato ries) [3]. Our X ray powder diffraction studies showed that the filler is fine polycrystalline graphite with a coherent scattering length (stack height) in the crys tallographic direction [002] of ≈30 nm.…”
mentioning
confidence: 93%
See 3 more Smart Citations